Serratia marcescens peritoneal dialysis peritonitis: a clinical case and therapeutic approach - Hmaidouch Nabil; Yacoubi Qods; Dkhissi Rihab; Ouzeddoun Naima; Benamar Loubna (Počki)
Peritoneal dialysis (PD) is increasingly used as a kidney replacement therapy in end-stage kidney disease, especially for its benefits in patient management and quality of life. However, PD peritonitis, particularly when caused by Serratia marcescens, can be a challenging complication that may require catheter removal. We present the case of a 17-year-old patient who had three PD peritonitis episodes in less than six months, caused by Serratia marcescens that led to catheter removal. This bacteria is known for its resistance to antibiotics and potential for systemic dissemination, making prompt recognition and management crucial. Catheter removal may be necessary early on to prevent further complications and improve patient outcomes.